The influence of fatty acids in vitro on mammalian cells from species differing in their fatty acyl desaturase capabilities. - Giangregorio, Alfredo (My University, 1991)
Numerous studies have assessed the effects of single fatty acids on various aspects of lipid metabolism, particularly cancer. Established cell lines have largely been used for this purpose. The choice of control cells. however, has often been inappropriate. There is also a surprising lack of knowledge of the effects of fatty acids in the "real world", in which normal cells in vivo are presented with mixtures of dietary fatty acids. Before transformed cells can be used as models of disease states, it is essential to fully understand fatty acid metabolism in normal (control) cells. Only then can experimental findings be extrapolated to the clinical situation with some certainty. This thesis has therefore, assessed the effects of exogenous fatty acid mixtures on the growth/viability of normal mammalian tissues all cultured under standard conditions, and attempted to elucidate the mechanisms underlying such effects. As different mammalian species exhibit different fatty acyl desaturase capabilities, cells from three species were chosen, viz. rat, Man and cat, with desaturase capability decreasing with species, respectively. A wide range of different cell types from each species were studied due to the known differences in their lipid ( Abbreviation abstract )
A Thesis submitted to the Faculty of Medicine, in Fulfilment of the Requirements for the Degree of Doctor of Philosophy
Keywords: Fatty Acids.